Implementation of Career Transition Programme in Vocational Skills for Students with Learning Disabilities - Mohamad Fitri Tordin; Mohd Mokhtar Tahar (Department of Special Education, 2021)
The aim of this research is to investigate the implementation programme from three (3) objectives namely identifying the parents’ (family) level of cooperation and the level of cooperation given by employers (industry) also the relationship between the two parties. A quantitative method based on Ecological Theory and Taxonomy for Transition Programming Model. In ensuring validity, the questionnaire was reviewed by an expert who is a university lecturer and also well-versed in the Special Education field. In terms of reliability, all of the items have the Cronbach Alpha coefficient of (> 0.65). Purposive sampling was used where 40 participants were included. Descriptive statistics was used to identify the percentage (%) and frequency (f) of respondents’ and inferential statistics well as Spearman Correlation Test were used to explain and test the hypothesis. The findings show that the mean scores for both the level of cooperation given by parents (family) and the level of cooperation given by employers (industry) are very high. However, there is no linear relationship (low level) between the cooperation given by parents (family) and employers (industry). In conclusion, this programme should be implemented in government and non-government school especially schools with Special Education Integration Programme with the cooperation from all parties.